Stochastic electron heating in an interference field of several laser pulses of a picosecond duration. (8th January 2019) - Bochkarev, S G; d'Humières, E; Tikhonchuk, V T; Korneev, Ph; Bychenkov, V Yu
Abstract: Efficient electron acceleration and heating is demonstrated in a multimode structure created by interference of several laser beams of a relativistic intensity and a picosecond duration near a sharp target boundary. Electron energization proceeds in two steps, with a slow stochastic heating followed by a fast regular acceleration in a resonance interaction with one of wave packets. It results in formation of a population of energetic electrons with an exponential distribution in energy characterized by a high effective temperature and a sharp cutoff. Hot electron characteristics depend on the number of crossing laser beams and their respective angles. This process is an example of efficient electron heating in vacuum by electromagnetic fields without participation of electrostatic plasma waves. It might contribute to creation of a superthermal particle population with an effective temperature significantly exceeding the common ponderomotive scaling.